One-way perspective explosion-proof glass and preparation method thereof

Through modified material technology, the compressive strength, flexural strength, thermal expansion coefficient and flame retardancy of glass are improved, and the problem of insufficient performance of existing glass in high-rise buildings is solved, and a higher performance unidirectional perspective explosion-proof glass is achieved.

CN119528453AActive Publication Date: 2025-02-28ZHONGSHAN XINGANJUE GLASS PROD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411786995.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

In the glass curtain wall design of high-rise buildings, existing glass has insufficient flexural strength, compressive strength, flame retardant resistance and expansion resistance, making it difficult to meet multiple requirements such as wind loads, earthquakes and fires.

Method used

One-way perspective explosion-proof glass was prepared by using modified castor oil polyol and isocyanate propyltriethoxysilane modified acrylic powder and lanthanum oxide combined with modified polyurethane resin. This method improves the compressive strength, flexural strength, thermal expansion coefficient and flame retardancy of the glass by modifying the material.

Benefits of technology

It achieves high compressive strength, flexural strength, low thermal expansion coefficient and good flame retardant properties of glass, meeting the multiple performance requirements of high-rise buildings for glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of glass, and provides one-way perspective explosion-proof glass and a preparation method thereof.The preparation method comprises the following steps that (1) a glass substrate is cleaned to obtain a pretreated glass substrate, (2) one face of the pretreated glass substrate is evenly coated with a peep-proof component, after coating is completed, baking is conducted for 10-15 min at the temperature of 240-260 DEG C, and then the glass substrate is dried to obtain the one-way perspective explosion-proof glass. The peep-proof component is hardened into the peep-proof layer; (3) uniformly coating the surface of the peep-proof layer with an explosion-proof component, baking for 10-15 minutes at the temperature of 190-200 DEG C, and hardening the explosion-proof component into an explosion-proof membrane to obtain a glass crude product; (4) putting the glass crude product into an intermediate frequency furnace, raising the temperature of the intermediate frequency furnace to 450-470 DEG C, heating for 10-15 minutes, and hardening and forming; and cooling and cleaning to obtain the one-way perspective explosion-proof glass. The glass provided by the invention has strong peep-proof, explosion-proof, compression-resistant and fracture-resistant capabilities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass, and in particular relates to a one-way perspective explosion-proof glass and a preparation method thereof. Background Art

[0002] Glass is widely used for its excellent light transmittance, sound insulation, relatively light weight and easy installation. However, as a typical brittle material, although glass is strong, it is also easy to break. Especially when it encounters strong explosion pressure or severe impact, it may break quickly and produce high-speed flying fragments, which may not only cause harm to personnel, but also pose safety risks to surrounding structures and facilities. Therefore, in order to protect personnel safety and property from damage, it is crucial to improve the ability of glass to resist impact and explosion.

[0003] In the design of glass curtain walls for high-rise buildings, glass needs to have good flexural strength, compressive strength, flame resistance and expansion resistance. The glass curtain walls of these buildings must not only withstand external forces such as wind loads and earthquakes, but also provide effective fire barriers in the event of a fire and maintain structural integrity under drastic temperature changes. Currently, there are the following problems with glass on the market: (1) Glass curtain walls for high-rise buildings need to withstand wind loads and other external forces. If the flexural strength is insufficient, the glass may break, which not only affects the appearance but also poses a safety hazard. (2) Although the compressive strength of glass is relatively high, in actual applications, due to its brittleness and uneven stress distribution, local areas may not be able to withstand large pressures and may be damaged. (3) In the event of a fire, glass curtain walls or partitions need to have sufficient fire resistance to prevent the spread of flames and smoke and protect personnel safety. (4) The thermal expansion coefficient of glass is small, but when the temperature changes drastically, especially when the temperature changes rapidly from low to high temperatures, large thermal stress will be generated inside the glass, causing cracks or breakage.

[0004] In order to improve the performance, explosion-proof glass currently on the market has explosion-proof layers on both sides of the base glass, which not only increases the cost but also loses the transparency of the glass.

[0005] Therefore, there is an urgent need for a one-way perspective explosion-proof glass and a preparation method thereof. Summary of the invention

[0006] The purpose of the invention is to provide a one-way perspective explosion-proof glass and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing one-way perspective explosion-proof glass comprises the following steps: (1) Clean the glass substrate to obtain a pre-treated glass substrate: (2) The anti-peeping component is evenly applied on one side of the pre-treated glass substrate. After the coating is completed, it is baked at a temperature of 240-260° C. for 10-15 minutes, and the anti-peeping component is hardened into an anti-peeping layer. The thickness of the anti-peeping layer is 8-12 μm; The anti-peeping component includes the following components in parts by weight: 100-110 parts of modified mixed powder, 5-10 parts of titanium dioxide, 32-35 parts of polyvinyl acetal, 42-45 parts of polyurethane acrylate, 12-15 parts of zinc oxide, 15-17 parts of tin oxide, 15-20 parts of AZO, 5-10 parts of ITO, and 10-12 parts of film-forming agent; (3) The explosion-proof component is evenly coated on the surface of the anti-peeping layer, and baked at a temperature of 190-200° C. for 10-15 minutes, so that the explosion-proof component is hardened into an explosion-proof film with a thickness of 1.5-1.7 μm, thereby obtaining a crude glass product; (4) Place the crude glass in a medium frequency furnace, heat the medium frequency furnace to 450-470°C, heat for 10-15 minutes, and harden it into shape; cool and clean it to obtain one-way transparent explosion-proof glass.

[0008] Furthermore, the preparation method of the modified mixed powder comprises the following steps: (1) Mixing modified castor oil polyol and isocyanate propyl triethoxysilane, reacting at 40-45° C. for 2-3 hours, and obtaining a reaction product; (2) The reaction product, the mixed powder and ethanol are mixed, reacted at 50-55° C. for 4-6 hours, and the ethanol is removed by vacuum rotary evaporation to obtain a modified mixed powder.

[0009] Furthermore, the amount of modified castor oil polyol is calculated based on OH molar amount, the amount of isocyanate propyl triethoxy silane is calculated based on NCO molar amount, and the molar ratio of modified castor oil polyol to isocyanate propyl triethoxy silane is (2.2-2.7):1.

[0010] Furthermore, the weight ratio of the reaction product, the mixed powder and ethanol is 1:(90-95):(400-450).

[0011] Furthermore, the mixed powder comprises the following components in parts by weight: 38-43 parts of acrylic powder, 50-55 parts of SiO2, and 5-10 parts of lanthanum oxide.

[0012] At present, silica is added to the privacy films on the market to improve the compressive strength of glass, but it still cannot meet the requirements of high-rise buildings for high compressive strength of glass. The present invention attempts to add acrylic powder and lanthanum oxide at the same time to improve the compressive strength of glass, but the effect is not ideal. By modifying the three materials with modified castor oil polyol and isocyanate propyl triethoxysilane, the dispersibility of the three powders and the compatibility with other components can be improved, thereby improving the compressive strength of glass. The reaction of modified castor oil polyol and isocyanate propyl triethoxysilane introduces organic functional groups to the surface of the powder. This surface modification can significantly improve the compatibility between inorganic particles and organic polymer matrix, reduce the agglomeration phenomenon between particles, and thus improve its dispersibility in the final composite material. Through the above chemical reaction, an intermediate product with organic-inorganic hybrid characteristics is formed. These hybrid particles not only inherit the physical properties of the original inorganic powder (such as hardness, optical properties, etc.), but also obtain flexibility and good processing properties from the organic part. At the same time, the flexural strength of the glass is improved.

[0013] Further, the explosion-proof component includes the following components in parts by weight: 35-39 parts of SiO2, 8-13 parts of lanthanum oxide, 55-58 parts of modified polyurethane, 20-25 parts of acrylic resin, 6-8 parts of pressure-sensitive adhesive, 5-10 parts of titanium dioxide, 3-7 parts of potassium dihydrogen phosphate, 6-9 parts of cerium oxide, and 4-8 parts of film-forming agent; Furthermore, the preparation method of the modified polyurethane resin comprises the following steps: (1) Add polyetheramine dropwise to polyisocyanate, react at 45-50°C for 1-2h, then add polyether polyol, raise the temperature to 75-80°C and react for 2-3h to obtain a prepolymer; (2) Add γ-aminopropyltriethoxysilane to the prepolymer and react at 45-50° C. for 2-3 hours to obtain a modified polyurethane resin.

[0014] Furthermore, the polyether polyol is a mixture of polyether polyol A (model HSH-204) with a hydroxyl value of 265-300 mgKOH / g, polyether polyol B (model 153-188) with a hydroxyl value of 153-188 mgKOH / g, and polyether polyol C (model HSH-215) with a hydroxyl value of 68-83 mgKOH / g in a weight ratio of 1: (1.2-1.5): (0.5-0.8). The mixture is purchased from Nantong Jiuze Chemical Co., Ltd.

[0015] In order to make the explosion-proof layer better combined with the surface of the privacy layer, the present invention modifies the polyurethane. By introducing specific functional groups, the adhesion between the polyurethane and the substrate (privacy film) can be enhanced, which helps to ensure that the explosion-proof layer is firmly adhered to the privacy film. At the same time, it was unexpectedly found that the thermal expansion coefficient of the glass can be improved by modifying the polyurethane. Polyisocyanate reacts with polyetheramine to form a prepolymer containing urethane bonds. These bonds have high rigidity and strong cohesion, which can limit the movement of molecular segments, thereby reducing the volume change of the material when heated. By introducing γ-aminopropyltriethoxysilane, the prepared modified polyurethane resin has the characteristics of organic-inorganic hybridization. This structure not only improves the mechanical properties of the material, but also improves the interfacial compatibility between the organic component and the inorganic component. Better interfacial compatibility can reduce the stress concentration caused by the difference in thermal expansion coefficients between different components, so that the entire composite material expands or contracts more evenly when the temperature changes, thereby reducing the overall thermal expansion coefficient. At the same time, the flame retardancy of the glass is improved.

[0016] Furthermore, the polyisocyanate is at least one of diphenylmethane diisocyanate, methylcyclohexyl diisocyanate and isophorone diisocyanate.

[0017] Furthermore, the molar ratio of the NCO group in the polyisocyanate to the total active hydrogen in the polyether polyol and the polyether amine is (2-2.5):1.

[0018] Furthermore, the molar ratio of the NCO group in the prepolymer to the active hydrogen in γ-aminopropyltriethoxysilane is (0.7-0.9):1.

[0019] The invention provides one-way perspective explosion-proof glass prepared by the preparation method.

[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention attempts to add acrylic powder and lanthanum oxide at the same time to improve the compressive strength of glass, but the effect is not ideal. By modifying the three materials with modified castor oil polyol and isocyanate propyl triethoxysilane, the dispersibility of the three powders and the compatibility with other components can be improved, thereby improving the compressive strength of the glass. At the same time, the flexural strength of the glass is improved.

[0021] 2. The present invention modifies polyurethane and introduces specific functional groups to enhance the adhesion between polyurethane and the substrate (privacy film), which helps to ensure that the explosion-proof layer adheres firmly to the privacy film. It is also unexpectedly found that the thermal expansion coefficient and flame retardancy of glass can be improved by modifying polyurethane. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The raw materials used in the following examples of the present invention are all commercially available products: Glass substrate, Zhengzhou Dongyao Glass Co., Ltd., 12mm tempered glass.

[0024] Titanium dioxide, Zhejiang Zhiti Nano-Micro New Materials Co., Ltd., model ZT05.

[0025] Polyvinyl acetal, brand: Sigma-Aldrich, product number: 182680.

[0026] Polyurethane acrylate, Guangzhou Jingtu Environmental Protection Materials Co., Ltd., model P-6212.

[0027] Zinc oxide, Zhejiang Zhiti Nano-Micro New Materials Co., Ltd., model ZT-AZO.

[0028] Tin oxide, Beijing Dekedaojin Technology Co., Ltd., average particle size: 50nm, specific surface area: 14.2m 2 / g.

[0029] AZO, Beijing Dekedaojin Technology Co., Ltd., model DK444.

[0030] ITO, Beijing Dekedaojin Technology Co., Ltd., In2O3:SnO2=90wt%:10wt%.

[0031] Film former, BASF LOXANOLCA5330.

[0032] Isocyanatepropyltriethoxysilane, Cas: 24801-88-5.

[0033] Acrylic powder, Japan Daikin, 1000 mesh.

[0034] SiO2, Zhejiang Zhiti Nano-Micro New Materials Co., Ltd., model ZT-SP15P.

[0035] Lanthanum oxide, Zhejiang Zhiti Nano-Micro New Materials Co., Ltd., model ZT-La01.

[0036] Acrylic resin, brand McLean, item number L990045.

[0037] Pressure-sensitive adhesive, Linqu Sanjun Plastic Products Co., Ltd., UV pressure-sensitive adhesive, peel force 18N / 25mm.

[0038] Cerium oxide, Zhejiang Zhiti Nano-Micro New Materials Co., Ltd., model ZT-Ce02. Example 1

[0039] This embodiment provides a one-way perspective explosion-proof glass, and the preparation method thereof comprises the following steps: (1) Clean the glass substrate to obtain a pre-treated glass substrate: (2) The anti-peeping component is evenly applied on one side of the pretreated glass substrate. After coating, it is baked at a temperature of 250° C. for 15 minutes, and the anti-peeping component is hardened into an anti-peeping layer. The thickness of the anti-peeping layer is 10 μm. (3) The explosion-proof component is evenly coated on the surface of the anti-peeping layer, and baked at a temperature of 195° C. for 15 minutes. The explosion-proof component is hardened into an explosion-proof film with a thickness of 1.7 μm, thereby obtaining a crude glass product; (4) The crude glass is placed in a medium frequency furnace, the medium frequency furnace is heated to 460°C, and heated for 15 minutes to harden and form; cooled and cleaned to obtain a one-way transparent explosion-proof glass.

[0040] The anti-peeping component includes the following components in parts by weight: 105 parts of modified mixed powder, 8 parts of titanium dioxide, 33 parts of polyvinyl acetal, 44 parts of polyurethane acrylate, 13 parts of zinc oxide, 16 parts of tin oxide, 17 parts of AZO, 8 parts of ITO, and 11 parts of film-forming agent; The preparation method of the modified mixed powder comprises the following steps: (1) Mixing modified castor oil polyol and isocyanate propyl triethoxysilane, wherein the amount of the modified castor oil polyol is calculated based on the OH molar amount, the amount of the isocyanate propyl triethoxysilane is calculated based on the NCO molar amount, and the molar ratio of the modified castor oil polyol to the isocyanate propyl triethoxysilane is 2.5:1; reacting at 42° C. for 2.5 hours to obtain a reaction product; (2) Mixing the reaction product, mixed powder and ethanol in a weight ratio of 1:92:420, wherein the mixed powder includes the following components in parts by weight: 40 parts of acrylic powder, 52 parts of SiO2, and 7 parts of lanthanum oxide; reacting at 52° C. for 5 h, and removing the ethanol by vacuum rotary evaporation to obtain a modified mixed powder.

[0041] Modified castor oil polyol was purchased from Shanghai Shuyu Chemical Co., Ltd., model SY780, hydroxyl value 180.

[0042] The explosion-proof component includes the following components in parts by weight: 37 parts of SiO2, 10 parts of lanthanum oxide, 56 parts of modified polyurethane, 21 parts of acrylic resin, 7 parts of pressure-sensitive adhesive, 8 parts of titanium dioxide, 6 parts of potassium dihydrogen phosphate, 7 parts of cerium oxide, and 6 parts of film-forming agent; The preparation method of the modified polyurethane resin comprises the following steps: (1) Add polyetheramine dropwise to polyisocyanate, react at 48°C for 1.5 hours, then add polyether polyol, wherein the molar ratio of NCO groups in the polyisocyanate to the total active hydrogen in the polyether polyol and the polyether amine is 2.2:1; the weight ratio of the polyether polyol to the polyether amine is 17:22; the temperature is raised to 78°C and reacted for 2.5 hours to obtain a prepolymer; the polyisocyanate is isophorone diisocyanate.

[0043] (2) adding γ-aminopropyltriethoxysilane to the prepolymer, wherein the molar ratio of the NCO group in the prepolymer to the active hydrogen in the γ-aminopropyltriethoxysilane is 0.8:1; reacting at 48° C. for 2.5 hours to obtain a modified polyurethane resin.

[0044] The polyether polyol is a mixture of polyether polyol A (model HSH-204) with a hydroxyl value of 265-300 mgKOH / g, polyether polyol B (model 153-188) with a hydroxyl value of 153-188 mgKOH / g, and polyether polyol C (model HSH-215) with a hydroxyl value of 68-83 mgKOH / g in a weight ratio of 1:1.4:0.6. The polyether polyols were purchased from Nantong Jiuze Chemical Co., Ltd.

[0045] The polyetheramine has an EO / PO ratio of 6 / 29 and an HLB value of 2.8. Brand: McLean, item number: P939193. Example 2

[0046] This embodiment provides a one-way perspective explosion-proof glass, and the preparation method thereof comprises the following steps: (1) Clean the glass substrate to obtain a pre-treated glass substrate: (2) The anti-peeping component is evenly applied on one side of the pretreated glass substrate. After the coating is completed, it is baked at a temperature of 260° C. for 10 minutes, and the anti-peeping component is hardened into an anti-peeping layer. The thickness of the anti-peeping layer is 10 μm; (3) The explosion-proof component is evenly coated on the surface of the anti-peeping layer, and baked at a temperature of 200° C. for 10 minutes. The explosion-proof component is hardened into an explosion-proof film with a thickness of 1.7 μm, thereby obtaining a crude glass product; (4) The crude glass is placed in a medium frequency furnace, the temperature of the medium frequency furnace is raised to 450°C, and heated for 15 minutes to harden and form; cooled and cleaned to obtain a one-way transparent explosion-proof glass.

[0047] The anti-peeping component includes the following components in parts by weight: 110 parts of modified mixed powder, 5 parts of titanium dioxide, 35 parts of polyvinyl acetal, 42 parts of polyurethane acrylate, 15 parts of zinc oxide, 15 parts of tin oxide, 20 parts of AZO, 5 parts of ITO, and 12 parts of film-forming agent; The preparation method of the modified mixed powder comprises the following steps: (1) Mixing modified castor oil polyol and isocyanate propyl triethoxysilane, wherein the amount of modified castor oil polyol is calculated by OH molar amount, the amount of isocyanate propyl triethoxysilane is calculated by NCO molar amount, and the molar ratio of modified castor oil polyol to isocyanate propyl triethoxysilane is 2.2:1; reacting at 45° C. for 3 hours to obtain a reaction product; (2) Mixing the reaction product, mixed powder and ethanol in a weight ratio of 1:90:400, wherein the mixed powder comprises the following components in parts by weight: 43 parts of acrylic powder, 55 parts of SiO2 and 5 parts of lanthanum oxide; reacting at 55° C. for 6 hours, and removing the ethanol by vacuum rotary evaporation to obtain a modified mixed powder.

[0048] Modified castor oil polyol was purchased from Shanghai Shuyu Chemical Co., Ltd., model SY780, hydroxyl value 180.

[0049] The explosion-proof component includes the following components in parts by weight: 39 parts of SiO2, 13 parts of lanthanum oxide, 55 parts of modified polyurethane, 25 parts of acrylic resin, 8 parts of pressure-sensitive adhesive, 10 parts of titanium dioxide, 3 parts of potassium dihydrogen phosphate, 9 parts of cerium oxide, and 4 parts of film-forming agent; The preparation method of the modified polyurethane resin comprises the following steps: (1) Add polyetheramine dropwise to polyisocyanate, react at 50°C for 1 hour, then add polyether polyol, the molar ratio of NCO group in the polyisocyanate to the total active hydrogen in polyether polyol and polyetheramine is 2:1; the weight ratio of polyether polyol to polyetheramine is 18:23; heat to 80°C and react for 2 hours to obtain a prepolymer; the polyisocyanate is diphenylmethane diisocyanate.

[0050] (2) adding γ-aminopropyltriethoxysilane to the prepolymer, wherein the molar ratio of the NCO group in the prepolymer to the active hydrogen in the γ-aminopropyltriethoxysilane is 0.9:1; reacting at 50° C. for 2 hours to obtain a modified polyurethane resin.

[0051] The polyether polyol is a mixture of polyether polyol A (model HSH-204) with a hydroxyl value of 265-300 mgKOH / g, polyether polyol B (model 153-188) with a hydroxyl value of 153-188 mgKOH / g, and polyether polyol C (model HSH-215) with a hydroxyl value of 68-83 mgKOH / g in a weight ratio of 1:1.2:0.5. The polyether polyols were purchased from Nantong Jiuze Chemical Co., Ltd.

[0052] The polyetheramine has an EO / PO ratio of 6 / 29 and an HLB value of 2.8. Brand: McLean, item number: P939193.

[0053] Comparative Example 1 The difference between this comparative example and Example 1 is that the modified mixed powder is replaced by a mixed powder, and the mixed powder includes the following components in parts by weight: 40 parts of acrylic powder, 52 parts of SiO2, and 7 parts of lanthanum oxide.

[0054] Comparative Example 2 The difference between this comparative example and Example 1 is that the mixed powder includes the following components in parts by weight: 52 parts of acrylic powder, 30 parts of SiO2, and 17 parts of lanthanum oxide.

[0055] Comparative Example 3 The difference between this comparative example and Example 1 is that the anti-peeping component includes the following components in parts by weight: 95 parts of modified mixed powder, 18 parts of titanium dioxide, 44 parts of polyvinyl acetal, 33 parts of polyurethane acrylate, 16 parts of zinc oxide, 13 parts of tin oxide, 8 parts of AZO, 17 parts of ITO, and 11 parts of film-forming agent.

[0056] Comparative Example 4 The difference between this comparative example and Example 1 is that no polyetheramine is added to the modified polyurethane resin, and the weight proportion of the polyetheramine is replaced by the same weight proportion of polyether polyol.

[0057] Comparative Example 5 The difference between this comparative example and Example 1 is that the polyether polyol is a mixture of polyether polyol A with a hydroxyl value of 265-300 mgKOH / g, polyether polyol B with a hydroxyl value of 153-188 mgKOH / g and polyether polyol C with a hydroxyl value of 68-83 mgKOH / g in a weight ratio of 1:1:1.

[0058] Comparative Example 6 The difference between this comparative example and Example 1 is that the explosion-proof component includes the following components in parts by weight: 30 parts of SiO2, 17 parts of lanthanum oxide, 46 parts of modified polyurethane, 31 parts of acrylic resin, 7 parts of pressure-sensitive adhesive, 13 parts of titanium dioxide, 2 parts of potassium dihydrogen phosphate, 4 parts of cerium oxide, and 6 parts of film-forming agent.

[0059] Performance Testing The glasses prepared in Examples 1-2 and Comparative Examples 1-6 were used as samples to conduct the following performance tests.

[0060] 1. Flexural strength: prepare clean specimens with no surface defects; turn on the power switch, select the range, adjust the level, and place the specimen; adjust the bow clamp and select the loading speed; for testing, press the slide hammer travel switch, slide the slide hammer to the left, increase the load until the specimen breaks, the slide hammer automatically moves forward, and read the maximum load from the corresponding position of the slide hammer pointer; return the slide hammer to its original position, turn the slide hammer speed knob, and align the white line on the knob with "0": measure the thickness and width of the specimen at the break, accurate to 0.1mm.

[0061]

[0062] Where, Rf: ultimate flexural strength N / m2; P: load when the specimen breaks, N; L: distance between the support blades, 30mm; b: width of the specimen at the fracture, mm; h: thickness of the specimen at the fracture, mm.

[0063] 2. Compressive strength: The method is the same as the flexural strength test method. The specific calculation formula is:

[0064] Where, P: compressive strength limit, N / m2; F: maximum load when the material is broken, N; S: force-bearing area of ​​the material, m2.

[0065] 3. Flame retardant performance: Test the material according to the UL-94 vertical combustion method.

[0066] 4. Thermal expansion coefficient: The thermal expansion coefficient is tested by STD dilatometer in accordance with standard GB / T16920-2015.

[0067]

[0068] The one-way perspective explosion-proof glass of Examples 1-2 of the present invention not only has one-way perspective performance and explosion-proof performance, but also has excellent mechanical properties, low thermal expansion coefficient, and good flame retardancy. In particular, the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the various parts.

[0069] However, the comparative examples are significantly inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the mixed powder is not modified, and it can be seen that the mechanical properties of the glass are reduced. In comparative example 2, the mixed powder compounding scheme is not used, and it can be seen from the results that the mechanical properties are reduced. In comparative example 3, the ratio of the anti-peeping component is changed, and the mechanical properties are also affected. In comparative example 4, no polyetheramine is added to the modified polyurethane resin, and the thermal expansion coefficient increases. In comparative example 5, the ratio of the polyether polyol is changed, and the thermal expansion coefficient increases. In comparative example 6, the ratio of the explosion-proof component is different, and the thermal expansion coefficient increases and the flame retardancy decreases. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effects.

[0070] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing one-way perspective explosion-proof glass, characterized in that: The following steps are involved: (1) Clean the glass substrate to obtain a pre-treated glass substrate: (2) The anti-peeping component is evenly applied on one side of the pre-treated glass substrate. After the coating is completed, it is baked at a temperature of 240-260° C. for 10-15 minutes, and the anti-peeping component is hardened into an anti-peeping layer. The thickness of the anti-peeping layer is 8-12 μm; The anti-peeping component includes the following components in parts by weight: 100-110 parts of modified mixed powder, 5-10 parts of titanium dioxide, 32-35 parts of polyvinyl acetal, 42-45 parts of polyurethane acrylate, 12-15 parts of zinc oxide, 15-17 parts of tin oxide, 15-20 parts of AZO, 5-10 parts of ITO, and 10-12 parts of film-forming agent; (3) The explosion-proof component is evenly coated on the surface of the anti-peeping layer, and baked at a temperature of 190-200° C. for 10-15 minutes, so that the explosion-proof component is hardened into an explosion-proof film with a thickness of 1.5-1.7 μm, thereby obtaining a crude glass product; (4) Place the crude glass in a medium frequency furnace, heat the medium frequency furnace to 450-470°C, heat for 10-15 minutes, and harden it into shape; cool and clean it to obtain one-way transparent explosion-proof glass.

2. The method for preparing the one-way perspective explosion-proof glass according to claim 1, characterized in that: The preparation method of the modified mixed powder comprises the following steps: (1) Mixing modified castor oil polyol and isocyanate propyl triethoxysilane, reacting at 40-45° C. for 2-3 hours, and obtaining a reaction product; (2) The reaction product, the mixed powder and ethanol are mixed, reacted at 50-55° C. for 4-6 hours, and the ethanol is removed by vacuum rotary evaporation to obtain a modified mixed powder.

3. The method for preparing the one-way perspective explosion-proof glass according to claim 2, characterized in that: The amount of modified castor oil polyol is calculated based on OH molar amount, the amount of isocyanate propyl triethoxy silane is calculated based on NCO molar amount, and the molar ratio of modified castor oil polyol to isocyanate propyl triethoxy silane is (2.2-2.7):

1.

4. The method for preparing the one-way perspective explosion-proof glass according to claim 2, characterized in that: The weight ratio of the reaction product, the mixed powder and ethanol is 1:(90-95):(400-450).

5. The method for preparing the one-way perspective explosion-proof glass according to claim 4, characterized in that: The mixed powder comprises the following components in parts by weight: 38-43 parts of acrylic powder, 50-55 parts of SiO2, and 5-10 parts of lanthanum oxide.

6. The method for preparing the one-way perspective explosion-proof glass according to claim 1, characterized in that: The explosion-proof component includes the following components in parts by weight: 35-39 parts of SiO2, 8-13 parts of lanthanum oxide, 55-58 parts of modified polyurethane, 20-25 parts of acrylic resin, 6-8 parts of pressure-sensitive adhesive, 5-10 parts of titanium dioxide, 3-7 parts of potassium dihydrogen phosphate, 6-9 parts of cerium oxide, and 4-8 parts of film-forming agent.

7. The method for preparing the one-way perspective explosion-proof glass according to claim 6, characterized in that: The preparation method of the modified polyurethane resin comprises the following steps: (1) Add polyetheramine dropwise to polyisocyanate, react at 45-50°C for 1-2h, then add polyether polyol, raise the temperature to 75-80°C and react for 2-3h to obtain a prepolymer; (2) Add γ-aminopropyltriethoxysilane to the prepolymer and react at 45-50° C. for 2-3 hours to obtain a modified polyurethane resin.

8. The method for preparing the one-way perspective explosion-proof glass according to claim 7, characterized in that: The polyether polyol is a mixture of polyether polyol A with a hydroxyl value of 265-300 mgKOH / g, polyether polyol B with a hydroxyl value of 153-188 mgKOH / g and polyether polyol C with a hydroxyl value of 68-83 mgKOH / g in a weight ratio of 1: (1.2-1.5): (0.5-0.8).

9. The method for preparing the one-way perspective explosion-proof glass according to claim 8, characterized in that: The polyisocyanate is at least one of diphenylmethane diisocyanate, methylcyclohexyl diisocyanate and isophorone diisocyanate.

10. A one-way perspective explosion-proof glass made according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silane-terminated modified polyurethane resin, high-strength low-modulus modified polyurethane sealant and preparation method thereof

    CN111471155A

  • Peep-proof film and preparation method thereof

    CN112123881A

  • Production process of peep-proof and explosion-proof coated glass easy to clean

    CN114933421A

  • Modification method of filler for polyurethane heat-conducting structural adhesive, modified filler and polyurethane heat-conducting structural adhesive

    CN116640531A

  • Treating glass containers to prevent scattering of glass fragments on breakage

    GB1420172A